BDH1 identified by transcriptome has a negative effect on lipid metabolism in mammary epithelial cells of dairy goats - Mengke Ni; Saige Zang; Yihan Wang; Xiaochen Qin; Min Tian; Tiantian Xiong; Chong Chen; Yue Zhang; Jun Luo; Cong Li (BMC Genomics)
Abstract Background The 3-hydroxybutyrate dehydrogenase 1 (BDH1) mainly participates in the regulation of milk fat synthesis and ketone body synthesis in mammary epithelial cells. In our previous study, BDH1 was identified as a key candidate gene regulating lipid metabolism in mammary glands of dairy goats by RNA-seq. This study aimed to investigate the effect of BDH1 on lipid metabolism in mammary epithelial cells of dairy goats (GMECs). Results The results suggest that BDH1 plays a significant role in reducing triacylglycerol content and lipid droplet accumulation in GMECs (p < 0.05). Overexpression of BDH1 significantly decreased the expression of lipid metabolism-related genes (SREBF1 and GPAM) and reduced the levels of C14:0 and C17:1, while increasing FABP3 expression and C10:0 concentration (p < 0.05). Interference with BDH1 significantly increased the expression of SREBF1 and GPAM and the concentration of C14:0, C15:1, and C20:1, but significantly decreased FABP3 and C18:0 (p < 0.05). Treatment of GMECs with β-hydroxybutyric acid (R-BHBA) significantly decreased the expression of FASN, ACACA, LPL, SREBF1, FABP3, ACSL1, GPAM, DGAT1, and triacylglycerol content, while significantly increasing the expression of BDH1 (p < 0.05). Interference with BDH1 rescued the reduction of cellular TAG content and the expression of FASN, LPL, SREBF1, ACSL1, and GPAM in BHBA-treated GMECs. Conclusion In conclusion, BDH1 negatively regulates lipid metabolism in mammary glands of dairy goats. Furthermore, it may mitigate the inhibitory effect of R-BHBA on lipid metabolism in GMECs. Graphical Abstract BDH1 serves as a negative regulator of milk lipid synthesis in GMECs, and BDH1 counteracts the inhibitory effect of R-BHBA on lipid synthesis in mammary epithelial cells of dairy goats.